2022
DOI: 10.31332/lkw.v0i0.3491
|View full text |Cite
|
Sign up to set email alerts
|

Cohesive Devices Used in Argumentative Essays by Undergraduate EFL Learners

Abstract: Cohesive devices are crucial points recognized as essential features of a good essay, yet employing them in an essay appropriately becomes problematic for learners. This study analyzes qualitatively cohesive devices to investigate EFL learners. It aims at examining how EFL learners apply cohesive devices in argumentative essays, the frequencies of cohesive devices errors in their writings, and the possible causes of EFL learners to produce cohesive devices. Twenty-five learners of the Department of Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The findings of this current study are consistent with prior research, such as that conducted by Fatimah and Yunus (2014), Rokhaniyah et al (2022) and Warna et al (2019), which also identified repetition as the most commonly used lexical cohesive device among students. This observation reveals a significant trend in student writing practices, suggesting a reliance on repetition as a primary strategy for achieving cohesion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this current study are consistent with prior research, such as that conducted by Fatimah and Yunus (2014), Rokhaniyah et al (2022) and Warna et al (2019), which also identified repetition as the most commonly used lexical cohesive device among students. This observation reveals a significant trend in student writing practices, suggesting a reliance on repetition as a primary strategy for achieving cohesion.…”
Section: Discussionsupporting
confidence: 92%
“…Halliday and Hasan (1976), in their foundational work on cohesion, noted that these devices often contribute to a deeper level of cohesion and coherence, and that proficient writers tend to use these devices more frequently. Therefore, while this research aligns with Fatimah and Yunus (2014), Rokhaniyah et al (2022) and Warna et al (2019) in identifying repetition as the primary lexical cohesive device used by students, it also underscores the need, highlighted by other researchers, for students to diversify their use of cohesive devices. It suggests that instruction in academic writing should include a focus on teaching a broader range of lexical cohesion strategies, to help students produce more engaging, coherent, and sophisticated texts.…”
Section: Discussionsupporting
confidence: 79%
“…Cohesion refers to the resources within the language that provide continuity in a text, above and over that is provided by clause structures and clause complexes (Ary Indrawan, 2014;Rokhaniyah et al, 2022;Sidabutar, 2021). Therefore, cohesive relations are non-structural relations which help the hang together.…”
Section: Introductionmentioning
confidence: 99%
“…In comparing the writing of native English learners and non-native English learners, research has shown that non-native speakers use fewer cohesive patterns, while Asian second language learners share similar cohesion patterns [2,3].…”
Section: Introductionmentioning
confidence: 99%